Educational Competences in Croatian Higher Education towards a Knowledge Society - Božić, Jasmina; Boras, Damir; Srbljinović, Armano (2007)
The paper examines higher education competences in Croatia in the context of the national aspiration to become knowledge society in the process of the European integration. Particularly since the Lisbon European Council in 2000 and the Councils in Stockholm (2001) and Barcelona (2002), with the gradual advancement of European educational competences framework towards the realisation of the ambitious objective of making EU 'the most competitive and dynamic knowledge-based economy in the world', the role and substance of higher education in Croatia have been changing with accelerated speed. Authors set out to explore the understanding and presentation of educational competences in Croatian fledgling knowledge society, in the context of European educational policy reforms for knowledge society and the day and age educational policies in Croatia. Starting from the European reference standards, authors constructed a research instrument and conducted a preliminary research at the University of Zagreb with a view to explore how the faculties present their study programmes in terms of basic educational competences to be acquired by their students. The findings are based on official documents of the faculties' web-sites, and proposals for improvement are presented.
Projekt MZOS
Projekt MZOS
ENG